2016
DOI: 10.1371/journal.pone.0153928
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Reactivation of BCAII Enzyme from Denatured and Molten Globule States by Eukaryotic Ribosomes and Domain V rRNAs

Abstract: In all life forms, decoding of messenger-RNA into polypeptide chain is accomplished by the ribosome. Several protein chaperones are known to bind at the exit of ribosomal tunnel to ensure proper folding of the nascent chain by inhibiting their premature folding in the densely crowded environment of the cell. However, accumulating evidence suggests that ribosome may play a chaperone role in protein folding events in vitro. Ribosome-mediated folding of denatured proteins by prokaryotic ribosomes has been studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
(75 reference statements)
0
7
0
Order By: Relevance
“…Several studies have demonstrated that the ribosome is itself capable of assisting in the folding of proteins spanning a wide range of folds and functions [1]. The protein-folding ability of the ribosome appears to be a universal one and has been demonstrated with ribosomes isolated from a wide range of sources including eubacteria, archaebacteria, eukaryotes (yeast, rat liver, and wheat germ), rabbit reticulocyte, bovine mitochondria, and mitochondria of the parasite Leishmania donovani [2][3][4][5][6][7][8][9]. These studies have also established that the chaperoning ability of the bacterial ribosome originates from the peptidyl transferase center that resides in domain V of the 23S rRNA of the bacterial large ribosomal subunit.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that the ribosome is itself capable of assisting in the folding of proteins spanning a wide range of folds and functions [1]. The protein-folding ability of the ribosome appears to be a universal one and has been demonstrated with ribosomes isolated from a wide range of sources including eubacteria, archaebacteria, eukaryotes (yeast, rat liver, and wheat germ), rabbit reticulocyte, bovine mitochondria, and mitochondria of the parasite Leishmania donovani [2][3][4][5][6][7][8][9]. These studies have also established that the chaperoning ability of the bacterial ribosome originates from the peptidyl transferase center that resides in domain V of the 23S rRNA of the bacterial large ribosomal subunit.…”
Section: Introductionmentioning
confidence: 99%
“…Urea, a chemical denaturant, primarily disrupts hydrophobic interactions and hydrogen bonds, while guanidinium chloride can additionally interfere with electrostatic interactions. 31,34 pH, a relatively milder denaturant, mainly affects the ionization states of certain amino acids in a protein. Therefore, pH-sensitivity of a protein inform us about the contribution of ionic interactions in its stability.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, pH-sensitivity of a protein inform us about the contribution of ionic interactions in its stability. 31 On the other hand, thermal denaturation disrupts noncovalent bonds and destabilizes the folded state by increasing the protein's kinetic energy and mainly disrupting hydrophobic interactions. 31 Understanding these differences helps researchers interpret the observed changes in protein structure and function upon denaturation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 This folding activity has been shown to promote productive folding from denatured and MG states. [41][42][43] Concerning apoflavodoxin, first results show that at physiological ionic strength the ribosome restrains formation of the off-pathway MG of F44Y apoprotein and forces the nascent chain towards the native state. 44 As MG off and the on-pathway folding intermediate of F44Y apoflavodoxin are concurrently present at physiological ionic strengths (Fig.…”
Section: Formation Of Concurrent Folding Intermediates In a Cellular ...mentioning
confidence: 99%